A STUDY ON AWARENESS ABOUT BREAST CANCER AND PRACTICE OF BREAST SELF-EXAMINATION AMONG ARTS AND SCIENCE STUDENTS, CHENNAI - A, Jenifar Monisha.; Sarathi , Sathiyalatha; Hemavathy, V.; H , Hema. V.; B , Pandian; Nightingale, Florence (South Eastern European Journal of Public Health, 2025)
Introduction: Breast cancer remains one of the most prevalent forms of cancer affecting women globally, with significant implications for public health. This study aims to assess the awareness about breast cancer and practice of breast self-examination among arts and science students, Chennai. Methods: A study used cross-sectional study design. The sample size consisted of 100 students selected through simple random sampling. The Institutional Ethics Committee authorized this study. The inclusion criteria were students within the age group of 18–24 years, and the exclusion criteria included those with a history of breast cancer or prior formal training in BSE. Results: The study findings revealed that awareness levels among participants varied, with 50% showing moderate awareness, 30% mild awareness, and 20% adequate awareness. While 80% had heard of breast cancer and 70% were aware of Breast Self-Examination (BSE), only 30% had ever practiced BSE. Additionally, 75% believed BSE aids in early detection, but only 40% had been taught how to perform it. Half of the participants were unaware of breast cancer's risk factors and symptoms. Conclusions: The study concluded that while most participants are aware of breast cancer and Breast Self-Examination (BSE), many do not regularly practice BSE. Even though most know about breast cancer and its prevention, many lack understanding of key aspects such as risk factors, symptoms, and the importance of early detection.